EFFECT OF ORGANIZATIONAL CULTURE INTENSITY ON JOB SATISFACTION - Prasiska Ramadyaning Utami; Maria Kristine Sitohang (Universitas Airlangga, 2019)
Background: Organizations need to pay attention to the job satisfaction of their members to achieve their goals. In 2011, the Airlangga Healthcare Center surveyed job satisfaction with the target of 80%. However, the target has not been achieved. Job satisfaction can be affected by several factors, and one of them is the culture within the organization.Aim: This study aims to analyze the effect of organizational culture intensity towards job satisfaction of the Airlangga Healthcare Center’s employees.Method: This study was conducted in November 2011 – June 2012 with a cross-sectional research design. The sample of the study used the population total technique. The independent variable of the research was the organizational culture intensity. While the dependent variable was job satisfaction. The data were analyzed descriptively by employing cross-tabulation analysis between organizational culture intensity and job satisfaction.Results: The most influential aspect of the organizational culture was cooperation that reached 73.9%. Job satisfaction aspects with a very satisfying level were job and co-worker aspects that reached 78.3%. The most influential aspect of organizational cultures that affect job satisfaction is trust that amounted to 83.3%. However, the organizational cultures affect job satisfaction with a percentage of 92.3% overall.Conclusion: The research concludes that the organizational culture intensity is a factor that affects job satisfaction of the employees at the Airlangga Healthcare Center. The recommendation for the organization is to improve the togetherness aspect of organizational cultures.Keywords: organizational culture intensity, job satisfaction, organization.